2012
DOI: 10.1016/j.bbr.2012.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Delayed developmental changes in neonatal vocalizations correlates with variations in ventral medial hypothalamus and central amygdala development in the rodent infant: Effects of prenatal cocaine

Abstract: While variations in neonatal distress vocalizations have long been shown to reflect the integrity of nervous system development following a wide range of prenatal and perinatal insults, a paucity of research has explored the neurobiological basis of these variations. To address this, virgin Sprague-Dawley rats were bred and divided into three groups: (1) untreated, (2) chronic-cocaine treated (30mg/kg/day, gestation days (GDs) 1–20); or (3) chronic-saline treated (2mg/kg/day, GDs 1–20). Pregnant dams were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 102 publications
2
16
1
Order By: Relevance
“…Thus, not only distributional changes in GluR1 and GluR2 but also projection pattern changes in OSNs should be further examined in Crmp4 ‐KO mice to clarify the precise roles of CRMP4 in the formation of the odor map. In addition, other brain areas such as the ventral medial hypothalamus and central amygdala, which are reported to be associated with production of UVs after olfactory stimulation (Cox et al ., ), have a potential for contributing to abnormal UV emission in Crmp4 ‐KO pups. It is also interesting to examine whether the observed changes in neuronal activity in the neonatal OB could produce any long‐term changes in OB function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, not only distributional changes in GluR1 and GluR2 but also projection pattern changes in OSNs should be further examined in Crmp4 ‐KO mice to clarify the precise roles of CRMP4 in the formation of the odor map. In addition, other brain areas such as the ventral medial hypothalamus and central amygdala, which are reported to be associated with production of UVs after olfactory stimulation (Cox et al ., ), have a potential for contributing to abnormal UV emission in Crmp4 ‐KO pups. It is also interesting to examine whether the observed changes in neuronal activity in the neonatal OB could produce any long‐term changes in OB function.…”
Section: Discussionmentioning
confidence: 99%
“…Mean vocalization measures assessed included total number of USVs, average peak frequency, standard deviation of frequency, average amplitude at the peak frequency, and standard deviation of amplitude of USVs emitted by pups on each respective test day. These measures were chosen as a priori based on recent findings suggesting CC-exposed offspring emit fewer USVs on PND 1 [23], and frequency modulation [19;20] and amplitude of USVs [21] may be important cues for maternal approach and response. To account for multiple comparisons (dam preference-like behavior correlated with five USV measures) we used the bonferroni correction method.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that neonates exposed gestationally to cocaine display altered vocalization patterns. In rodents and chickens, PCE can result in decreases in the number of vocalizations (Hahn et al, ; Cox et al, ; Lippard et al, ), while others have shown increases in USVs relative to controls; although this effect normalized soon after in rodents (Kabir et al, ; Zeskind et al, ). As in humans, others have shown that USV emitted from PCE‐exposed rodents also differ from their control peers in the acoustic structure, harmonics, duration, and pitch of the calls (Hahn et al, ; Cox et al, ; Zeskind et al, ).…”
Section: Animal Modelsmentioning
confidence: 99%